Discriminatory analysis of spring water supply direction. Issue 4 (May 2020) - Zhang, Xinhui; Xing, Liting; Zhao, Zhenhua; Yao, Chunmei; Xing, Xuerui; Deng, Zhong
Abstract: In this paper, 56 groups of underground water samples were collected in Baotu Spring Catchment, and a discriminant model was established to judge the recharge direction and aquifer of the four major spring groups. The results showed that Baotu Spring Group and Black Tiger Spring Group mainly recharge from southwest direction Ordovician karst water, Central south direction of Ordovician karst water respectively, and Five Dragon Pool Spring Group and Pearl Spring Group received from southwest direction and southeast direction Cambrian karst water supplement respectively. The research results are of great significance to the implementation of Jinan spring conservation and precise source replenishment measures. At the same time, it shows that the karst water system in northern China has the characteristics of uneven karst development.